On measuring warehouse work efficiency in third party logistic operations using highly subcontracted workforce - Strömberg, Ilmo (My University, 2015)
The subject of this thesis was given by a case company, which is a 3PL provider. In this context, warehouse logistics with highly subcontracted workforce was under microscope. The aim was to conceive warehouse work efficiency metrics which will be used as the basis of the Case company’s upcoming WMS. The theory part first looks at the research environment, which is in many respects different compared to that of traditional manufacturing operations. Video recordings were a big part of the empirical research, so the theory part focuses on the time and motion theory. The idea was to capture warehouse work’s current state by video camera and then to analyze the recordings from the current state perspective. For the analysis part, lean philosophy was used as a source of potential improvement solutions as they are always needed in tight competition. Also best practices on efficiency and performance measurement literature were searched and used. Using video recordings, different workflow analyses were conducted which revealed some process problems. Efficiency-wise, standard times were calculated representing current state’s average efficiency. Line based efficiency measurement proved to be the best, except for one customer where also sales unit examination was needed. For monitoring personal efficiency, the proposed metric is earned total price (defined in customer contract) per working hour.
Keywords: Efficiency Measurement; Key Performance Indicators; Warehouse Logistics; Lean; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|